Memorandum of understanding between Universiti Teknologi MARA and Chicken Ball Ball Rice Restaurant / Fakulti Pendidikan - Universiti Teknologi MARA, Fakulti Pendidikan (Universiti Teknologi MARA (UiTM), 2017)
Memorandum of understanding between Universiti Teknologi MARA and Chicken Ball Ball Rice Restaurant shall endeavour to network, strengthen, promote and develop collaborative efforts in South-East Asia Social Innovation projects on the basis of equality and mutual benefit.